Paraprobiotics and Postbiotics of Probiotic Lactobacilli, Their Positive Effects on the Host and Action Mechanisms: A Review - Teame, Tsegay; Wang, Anran; Xie, Mingxu; Zhang, Zhen; Yang, Yalin; Ding, Qianwen; Gao, Chenchen; Olsen, Rolf Erik; Ran, Chao; Zhou, Zhigang (Frontiers in Nutrition, 2020)
Lactobacilli comprise an important group of probiotics for both human and animals. The emerging concern regarding safety problems associated with live microbial cells is enhancing the interest in using cell components and metabolites derived from probiotic strains. Here, we define cell structural components and metabolites of probiotic bacteria as paraprobiotics and postbiotics, respectively. Paraprobiotics and postbiotics produced from Lactobacilli consist of a wide range of molecules including peptidoglycans, surface proteins, cell wall polysaccharides, secreted proteins, bacteriocins, and organic acids, which mediate positive effect on the host, such as immunomodulatory, anti-tumor, antimicrobial, and barrier-preservation effects. In this review, we systematically summarize the paraprobiotics and postbiotics derived from Lactobacilli and their beneficial functions. We also discuss the mechanisms underlying their beneficial effects on the host, and their interaction with the host cells. This review may boost our understanding on the benefits and molecular mechanisms associated with paraprobiotics and probiotics from Lactobacilli, which may promote their applications in humans and animals.